A pilot study on effect of adjunctive transcranial direct current stimulation on symptom domains of depression in patients with depressive disorder - Shipra Singh; Amit K Meena; Gautam Sharma; Smita N Deshpande (Industrial Psychiatry Journal, 2021)
Background: Depression is a highly prevalent condition and includes clusters of symptoms, namely, depressive cognition, anxiety, and visceral symptoms. Depressive symptoms often respond sub-optimally to pharmacotherapy. Adjunctive transcranial direct current stimulation (tDCS), a noninvasive brain stimulation modality, may improve depressive symptomatology. Aim: The aim of this study was to study the effect of tDCS as an augmentation strategy in depression and its various symptom domains. Materials and Methods: It is a prospective interventional study. Patients diagnosed with depressive disorder (based on International Classification of Disease- 10 criteria, diagnosed by treating psychiatrist), aged 18-70 years, who showed inadequate improvement on antidepressant selective serotonin reuptake inhibitors, were recruited after informed consent. Each participant was administered 20 sessions of tDCS over 2 weeks, each session of 20 min, with anode placement at left dorsolateral prefrontal cortex and cathode at right supraorbital region. Hamilton Rating Scale for Depression (HAM-D) was administered pre- and post-intervention to assess the change in symptoms. Results: Of a total of 35 participants, the mean score on HAM-D prior to and postintervention was 19.97 (standard deviation [SD] = 3.519) and 13.17 (SD = 3.365), respectively. The difference was statistically highly significant (P = 0.000) on paired t-test. All symptom domains of HAM-D, identified using the Cole and Motivala model (Cole et al., 2004), also showed significant reduction from pre-tDCS to post-tDCS scores (P = 0.000). Conclusion: Positive effect of tDCS on depressive symptoms, its tolerability and safety profile, and affordability makes it an effective therapeutic strategy in augmenting antidepressants in patients with depression. However, longer period studies with larger sample size may yield more generalizable results.